Rapid weight loss in the context of Ramadan observance: recommendations for judokas - Aloui, A.; Chtourou, H.; Briki, W.; Tabben, M.; Chaouachi, A.; Souissi, N.; Shephard, R. J.; Chamari, K. (Biology of Sport, 2016)
Judo is a weight-classified combat sport, and many athletes seek to compete at the lightest possible weight category to gain an advantage from competing against shorter/smaller, and supposedly weaker opponents. To achieve a desired weight, most judokas opt for rapid weight loss techniques. Short-duration maximal efforts are not greatly affected by "making weight", but prolonged and/or repeated exercise is significantly impaired. Negative effects on mood, ratings of perceived exertion, and cognitive function are also reported. Moreover, rapid weight loss reduces maximal cardiac output and glycogen stores, and impairs thermo-regulation. Limited empirical data suggest that Ramadan reduces judokas' performance, and this is likely to be exacerbated by attempts at rapid weight loss. Weight reduction during Ramadan tends to be counterproductive, and judokas who aim for a lower weight category are advised to attempt any desired reduction of body mass during the weeks leading up to Ramadan, rather than during the holy month.